Effects of translanguaging on science literacy among high school students - Guinto, Christian Genesis (American Journal of STEM Education, 2026)
This study examined the effects of translanguaging on science literacy among Grade 10 students in a multilingual Philippine classroom. Seventy-eight participants were assigned to a translanguaging instruction group (n=39), integrating Filipino and English, or a monolingual instruction group (n=39). ANCOVA results showed significantly higher post-test science literacy scores for the translanguaging group (adjusted M=37.21, SE=0.64) than the monolingual group (adjusted M=29.13, SE=0.64), F(1,75)=79.64, p<.001, partial η²=.515, controlling for pre-test scores. No significant interaction with language proficiency emerged (F(1,73)=0.36, p=.549). Cognitive engagement also showed a significant main effect (F(2,70)=3.26, p=.044, partial η²=.085). Findings indicate that translanguaging enhances science literacy across proficiency levels, with cognitive engagement moderating outcomes, supporting its adoption in linguistically diverse classrooms.